Variation of Indonesian Language Teaching Techniques in Islamic Elementary School - Jannah, Roudlotul (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2020)
This research is aimed to identify some techniques used to teach The Indonesian language for elementary school. This qualitative research is conducted in Miftahul Ulum elementary school which is located in Kepohbaru Bojonegoro. The data collection techniques consist of interview, questionnaire, and documentation. The result shows that there are 14 techniques used in the lower level and 13 techniques in the upper level. From the varied techniques applied, there are three techniques which support listening skill development, six techniques support speaking skill development, four techniques support reading skill development, and four techniques support writing skill development. The variations of using language teaching technique have implication in mapping methods and techniques before learning is implemented. The mapping should appropriate for the students’ development phase.